KOMPETENSI KEPRIBADIAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMA KORPRI JAYAPURA - Agnes Aryesam; Meylani Aljeinie Tijow; Florentina M. Panda (Universitas Cenderawasih, 2020)
This study aims to describe the personality competencies of principal in improving teachers’ performance at SMA Korpri Jayapura and also to describe the supporting and inhibiting factors. The approach used in this research is qualitative descriptive. The subjects for this research are the principal and all teachers. The data was collected through observation, in-depth interviews and documentation study which were then analyzed and tested for their validity using the triangulation method. The results showed that the implementation of the principal's personality competence at SMA Korpri Jayapura had not been going well according to the six indicators of personality competence, the principal had not been maximal in showing an example of time discipline and the inconsistent development of school programs. The supporting factors include: (a) the awareness of teachers to carry out their duties and responsibilities, (b) the independence of teachers in administration, (c) the existence of good cooperation with related agencies. While the inhibiting factor is the existence of other external factors outside of school that affect educational activities in schools. Keywords: The personality competencies of principal, Teachers’ performances